Comunidad, Sociedad: reflexiones desde la historia conceptual - Mazzola, Ignacio (Nómadas. Critical Journal of Social and Juridical Science, 2011)
In this paper we take as our subject the history of the modern concepts “community” and “society”, which relate to each other as asymmetric counterconcepts with different references although they have a common origin in the Aristotelian koinonía, the reference of which was the Greek polis. Departing from that consideration we ask whether the experience of which the differentiated concepts are indicatives and factors is purely and exclusively modern or if it is possible to find a “similar” experience in the past. In that case, we should be able to find the way in which that experience was then conceptualized. That takes us to analyze the social and political thought of Cicero and Saint Augustine, located both at the crossroad of different intellectual traditions and marked by specific historical circumstances. We conclude with a few reflections on the gains that social theory can expect from the history of concepts.